Extreme sensitivity of a topochemical reaction to cation substitution: SrVO2H versus SrV1-xTixO1.5H1.5 - Amano Patino, M; Zeng, D; Blundell, S; McGrady, J; Hayward, M (American Chemical Society, 2018)
The anion-ordered oxide-hydride SrVO2H is an antiferromagnetic insulator due to strong correlations between vanadium d electrons. In an attempt to hole-dope SrVO2H into a metallic state, a strategy of first preparing SrV1-xTixO3 phases and then converting them to the corresponding SrV1-xTixO2H phases via reaction with CaH2 was followed. This revealed that the solid solution between SrVO3 and SrTiO3 is only stable at high temperature. In addition, reactions between SrV0.95Ti0.05O3 and CaH2 were observed to yield SrV0.95Ti0.05O1.5H1.5 not SrV0.95Ti0.05O2H. This dramatic change in reactivity for a very modest change in initial chemical composition is attributed to an electronic destabilization of SrVO2H on titanium substitution. Density functional theory calculations indicate that the presence of an anion-ordered, tetragonal SrMO2H phase is uniquely associated with a d2 electron count and that titanium substitution leads to an electronic destabilization of SrV1-xTixO2H phases, which, ultimately, drives further reaction of SrV1-xTixO2H to SrV1-xTixO1.5H1.5. The observed sensitivity of the reaction products to the chemical composition of initial phases highlights some of the difficulties associated with electronically doping metastable materials prepared by topochemical reactions.